Haemangiopericytoma. Issue 2 (February 1984) - Panda, A.; Dayal, Y.; Singhal, V.; Pattnaik, N. K.
Abstract : Three cases of orbital haemangiopericytoma are presented. In one the tumour recurred after 22 years and in another after 4 months. Metastasis to the breast, which occurred in the third case, is probably the first to be reported. The management of the cases is discussed. The clinical importance of the haemangiopericytoma lies in its potentially malignant behaviour.